Inclusión educativa y rincón de la lectura en educación inicial nivel II del Centro Educativo Mercedes Quinde Burneo. Periodo 2023 - 2024 - Matailo Villavicencio, Julia Elizabeth (2024)
Promoting educational inclusion in the reading corner is important and effective. It allows learning to be adapted to better foster students' imagination and creativity while strengthening oral language skills essential for effective communication. Providing various materials such as stories, fables, songs, rhymes, pictograms, and puppets, can be achieved by using different materials in the reading corner, such as stories, fables, songs, rhymes, pictograms, and puppets, thus achieving good socio-educational integration. The present project aims to analyze the situation of educational inclusion and inclusive materials in the reading corner of the Early Childhood Education II level at the "Mercedes Quinde Burneo" Educational Center. The information was collected within the classroom through instruments such as the interview and observation sheet, framed within a qualitative descriptive approach. The research found that the teacher does have a reading corner, however, the lack of inclusive teaching materials prevents her from using it appropriately to integrate children in an inclusive classroom and thus respond to the diversity of learning styles of all children. This research aims to enhance the reading corner in early childhood education by creating a more inclusive and effective learning environment. Recognizing the vital role of reading, imagination, and creativity in early development, this study seeks to promote equal opportunities for all children. The ultimate goal is to develop a guide filled with fun activities that will help teachers foster educational inclusion within the reading corner, catering to the unique needs of each student at the 'Mercedes Quinde Burneo Educational Center'. Keywords: Inclusive classroom, childhood education, and inclusive materials, teaching guide, vital role of reading.